What's new in nutrition for adults with diabetes?. Issue 9 (September 2016) - Nwankwo, Robin; Funnell, Martha
Abstract : What should your staff members tell patients about how to plan meals to reach their glycemic, weight, and other targets? The current American Diabetes Association guidelines outlined in this article provide answers.